Business Ethics Index: Latin America - Tsalikis, John; Seaton, Bruce; Shepherd, Phillip L. (2014)
For almost 10 years, the Business Ethics Index (BEI) has measured consumers’ perceptions of business ethical behavior in the USA and numerous other countries. This article expands the BEI to five Latin American countries (Brazil, Bolivia, Mexico, Argentina, and Colombia). The BEI of Argentina and Bolivia were similar in magnitude to the USA, whereas those for Brazil, Colombia, and Mexico were distinctly higher. The component sub-indices showed divergent patterns. The major ethical concerns for Brazil and Bolivia concerned service, whereas Mexico and Argentina complained about overpricing.
Keywords: Argentina and Colombia; Mexico; Bolivia; Brazil; Latin America; Business Ethics; BEI; Business Ethics Index